A Quantitative Evaluation of Metacognitive Awareness among Business Administration Students - Awdah, Doha Al; Awdah, Doha Al; Jasmeen, Dr Sofia; Jasmeen, Dr Sofia; Alexander, Dr Asha (Archives of Business Research, 2017)
Purpose - The metacognitive approach is the new learning paradigm to enrich the standard of education in general and that of business education in particular The purpose of the study was to ascertain the views and opinions of Business Administration students regarding the metacognitive awareness. Design- A self-administered questionnaire was distributed to female undergraduate students. Statements cover between two major components, including knowledge about cognition and regulation of cognition. For analyzing the hypothesis, parametric as well as non-parametric test have been used. Findings –The students had a substantial awareness of metacognition and was correlated positively and significantly with their academic performance. There was no significant difference in the metacognitive awareness of undergraduate students based on their academic levels, majors and learning styles. This significant improvement on the academic performance of the students was due to the university adherence to the domains set by the national quality framework. Students on each academic level benefited by alignment of Learning Outcomes, Assessment Methods, and Teaching Strategy and attained increasing knowledge ,skills communication and information technology preparing them to be autonomous learners. Originality/Value – This paper contributes to the need for significance of metacognitive awareness among undergraduate students. The findings provide insight into students’ metacognitive skills and to adopt certain teaching strategies and assessment patterns for inculcating high order thinking in the students to prepare them as autonomous learners and engage lifelong earning among them